Direct D-atom Incorporation in Radicals: An Overlooked Pathway for Deuterium Fractionation - Nureshan Dias; Ranil M. Gurusinghe; Bernadette M. Broderick; Tom J Millar; Arthur G. Suits (The Astrophysical Journal, 2023)
Direct D-H exchange in radicals is investigated in a quasi-uniform flow employing chirped-pulse millimeter-wave spectroscopy. Inspired by the H-atom catalyzed isomerization of C _3 H _2 reported in our previous study, D-atom reactions with the propargyl (C _3 H _3 ) radical and its photoproducts were investigated. We observed very efficient D-atom enrichment in the photoproducts through an analogous process of D addition/H elimination to C _3 H _2 isomers occurring at 40 K or below. Cyclic C _3 HD is the only deuterated isomer observed, consistent with the expected addition/elimination yielding the lowest energy product. The other expected addition/elimination product, deuterated propargyl, is not directly detected, although its presence is inferred by the observations in the latter part of the flow. There, in the high-density region of the flow, we observed both isotopomers of singly deuterated propyne attributed to stabilization of the H+C _3 H _2 D or D+C _3 H _3 adducts. The implications of these observations for the deuterium fractionation of hydrocarbon radicals in astrochemical environments is discussed with the support of a monodeuterated chemical kinetic model.